Water Catchment Zone Mapping for Watershed Management in Gesing Sub-Watershed, Purworejo - Arief Wicaksono; Shandra S Pertiwi; Ade Febri Sandhini P; Prima Widayani (Politeknik Negeri Batam, 2019)
Water is a very important resource involved in almost all life processes on earth, especially for human life. The rapid growth of water consumption with a decrease in the quantity and quality of water sources certainly creates problems of water scarcity or even flooding, which already occurs in some areas of Indonesia. In the last decades, some areas in Purworejo District, Indonesia have experienced floods, landslides, and droughts. This condition indicates that there has been a water quantity problem in the watershed in Purworejo. This study tends to focus on water resource management in terms of management planning. The purpose of this research is to create a water catchment zone map with the integration of remote sensing methods and geographic information systems. Identification of potential water catchment considers several parameters, such as soil permeability, rainfall, soil surface type, slope, and groundwater level. The results map consists of five classes of water catchment zone in the Gesing Sub-watershed. The higher classes were found in the upper watershed and the center of the watershed, especially in the valley section of the river. The lower classes, such as in the center of the watershed were considered as suitable areas to protect the water quality. With the mapping of water catchment zone, it is expected that the government can make appropriate policies related to water resources management of each sub-watershed so that in the end the water supply problem-especially in terms of quantity-can be managed and controlled effectively.